Responding to the Endrew’s Decision: Measuring Meaningful Educational Benefit - Hartman, Deborah W. (Journal of the American Academy of Special Education Professionals, 2019)
The U.S. Supreme Court ruling, of March 2017, favored the plaintiff, Endrew F. in the "Endrew F. v. Douglas County School District" case. This decision strengthens the Rowley decision of 1982 and has raised the bar requiring an increased responsibility for Districts to provide programs to eligible students with disabilities the opportunity to make appropriately ambitious and measured progress. Utilizing methods of progress monitoring and determining the anticipated rate of improvement provides a firmer decision-making process to ensure educational benefit.